Light emitting diodes for agriculture : smart lighting - Gupta, S. Dutta (Springer, 2017)
This book presents a comprehensive treatise on the advances in the use of light-emitting diodes (LEDs) for sustainable crop production and describes the latest photomorphogenesis research findings. It introduces readers to the fundamentals and design features of LEDs applicable for plant growth and development and illustrates their advantages over the traditional lighting systems, including cost analyses. Further, it discusses a wide range of applications covering diverse areas of plant sciences relevant to controlled environment agriculture and in vitro plant morphogenesis. The chapters have been written by a team of pioneering international experts, who have made significant contributions to this emerging interdisciplinary field. The book will serve a valuable resource for graduate students, instructors, and researchers in the fields of horticulture, agricultural biotechnology, cell and developmental biology, and precision agriculture. It will also serve well professionals engaged in greenhouse and vertical farming.
Keywords: Light emitting diodes.; Agricultural innovations.; elektronické knihy; electronic books